Are global value chains merely global? The case of Chinese Provinces in global value chains. Issue 32 (9th July 2021) - Xie, Rui; Niu, Meng; Su, Bin; Ge, Jiali
ABSTRACT: We extend the measure of the global value chain (GVC) decomposition framework to the sub-national regional level based on a new Trans-national Inter-regional Input-Output (TIIO) table, which covers 30 Chinese provinces for 2007 and 2012. We answer the question whether fragmentation of GVCs is mainly national, regional or merely global by deriving the geographical distribution by province and the trends related to the production chain of a particular final good. Depending on whether the intermediate inputs cross borders for production or not, we further divide these production activities into GVC or non-GVC activities and identify the changing mechanism from the perspective of simple and complex GVC activities. We find that coastal provinces show a higher decline in nationalization compared to inland provinces. The degree of regionalization weakening of each province is generally the same, which is more evident in coastal provinces. Additionally, coastal provinces show a more significant decline of globalization compared to inland provinces. Regarding border crossing production-sharing activities, complex GVC embeddedness is the main mode of Chinese provinces. They, however, show signs of gradual weakening over time. This is more pronounced in the dynamic evolution of regionalization and globalization in coastal provinces.